Motivation as preparatory department students' personal readiness to learn Russian as a foreign language - Kozlovskaya, Ekaterina (2021)
The article covers motivation as a complex psychopedagogical process reflecting the level of preparatory department students' personal readiness to learn Russian as a foreign language. The article shows that teaching Russian is a complex multi-dimensional process closely linked to an individual's motivational abilities. The author analyzes educational and cognitive motivation along with motivation for foreign-language communication. The article describes the results of research on preparatory department students' personal motivation.